Eksplorasi Respon Netizen di Tiktok Terhadap Berita Bencana Alam di Sumatera Utara dan Aceh Tahun 2025 - Mhd Rafi Zhafran; Hasan Sazali (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2026)
The increasing use of TikTok as a platform for public interaction during natural disasters has transformed the way disaster-related information is disseminated and interpreted, yet studies examining the characteristics of netizen responses in this context remain limited. This study explores the patterns of netizen responses on TikTok to natural disasters in North Sumatra and Aceh in 2025. A qualitative descriptive approach was employed through virtual observation, digital documentation, and literature review, with primary data obtained from comments and viral content related to the Aceh Tamiang flood. Data were analyzed using the Computer-Mediated Communication and Stimulus-Organism-Response frameworks. The findings reveal diverse response patterns, including affective responses (empathy and solidarity), cognitive responses (criticism of government disaster management), and conative responses (encouragement of humanitarian action). The comments section functioned as a discursive space for shaping public opinion, while word cloud visualization and sentiment analysis highlighted dominant narratives of humanity and solidarity alongside institutional criticism. The novelty of this study lies in integrating qualitative digital discourse analysis with sentiment mapping to explain how TikTok facilitates participatory disaster communication and public opinion formation. The study concludes that TikTok plays a significant role in interactive disaster communication while simultaneously increasing the risk of misinformation in digital environments.